LEMBAGA PENANGANAN KORBAN TINDAK KEKERASAN - Daud Bahransyah (Sosio Informa, 2003)
(Domestic Violence Prevention Organization).There are many case of violence action to the children and woman have been gape. There aremany variation victims, such as light injury, mortally wounded and undergo of physical defect until died. In the below will be explained about how far this case will be handle.Key words ; domestic violence, prevention